FEATURES OF CELLULAR HUMORAL IMMUNITY DURING BONE TISSUE REGENERATION IN PATIENTS WITH CLOSED FRACTURES OF TUBULAR BONES - Khamdamov Bakhtiyor Zarifovich; Napasov Ilkhomjon Zubaidulloevich; Khamdamov Alisherjon Bakhtiyorovich (Scholar Express Journals, 2024)
Clinical and immunological comparison of the course of regenerative processes of bone tissue, carried out on the basis of a comparison of ultrasound data from the fracture zone and the obtained information from monitoring changes in immunological blood parameters, made it possible to identify a number of features of the body’s immunological reaction. This, to a certain extent, reflects the features of the course of bone tissue regeneration, which can be interpreted as possible effective prognostic markers. To conduct such an assessment, it may be most effective to apply principles and analyzes based on the rules of evidence-based medicine.
Keywords: Regeneration; Bone Tissue; Immunity